2023
DOI: 10.1093/cvr/cvad008
|View full text |Cite
|
Sign up to set email alerts
|

The longevity-associated BPIFB4 gene supports cardiac function and vascularization in ageing cardiomyopathy

Abstract: Aims The aging heart naturally incurs a progressive decline in function and perfusion that available treatments cannot halt. However, some exceptional individuals maintain good health until the very late stage of their life due to favourable gene-environment interaction. We have previously shown that carriers of a longevity-associated variant (LAV) of the BPIFB4 gene enjoy prolonged health spans and lesser cardiovascular complications. Moreover, supplementation of LAV-BPIFB4 via an adeno-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…The “rejuvenating” properties of the LAV-BPIFB4 were demonstrated in pre-clinical models, with a broad spectrum of protective effects towards different pathological conditions, including inflammatory status [ 23 ], cardiovascular problems [ 21 ] and Huntington’s disease [ 27 ]. Interestingly, recent evidence demonstrated that LAV delivery caused a rejuvenation of the hearts of old mice by a human equivalent of more than ten years [ 22 ]. Here, we demonstrated that the LAV gene therapy was also able to slow down the epigenetic age progression in nucleated blood cells of aged mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The “rejuvenating” properties of the LAV-BPIFB4 were demonstrated in pre-clinical models, with a broad spectrum of protective effects towards different pathological conditions, including inflammatory status [ 23 ], cardiovascular problems [ 21 ] and Huntington’s disease [ 27 ]. Interestingly, recent evidence demonstrated that LAV delivery caused a rejuvenation of the hearts of old mice by a human equivalent of more than ten years [ 22 ]. Here, we demonstrated that the LAV gene therapy was also able to slow down the epigenetic age progression in nucleated blood cells of aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although such a reduction was more evident in males, female mice showed the same trend, and the absence of a significant difference may be likely due to the smaller sample size compared to the male one. In support of a sex-independent action of the LAV therapy, its effect on the cardiac function was clearly demonstrated in both male and female mice [ 22 ]. Nonetheless, a sex-specific activity was previously ascribed to the BPIFB4 protein, which inversely correlated with the severity of the COVID-19 disease in men but not in women [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, removal of senescent cells by senolytics improves the overall functioning of the heart, even in aged mice ( 77 , 83 ). In a recent study Cattaneo et al reported the importance of longevity-associated BPIFB4 ( LAV-BPIFB4 ) gene in supporting cardiac function and vascularization in ageing cardiomyopathy ( 84 ). They demonstrated reduced LAV-BPIFB4 in older hearts and that gene therapy with LAV-BPIFB4 rescued cardiac function and myocardial perfusion in aged mice by improving microvasculature density and pericyte coverage.…”
Section: Ageing-induced Molecular Changes In Cardiovascular Cellsmentioning
confidence: 99%